Saturday Night at the Lakeside Supper club : a novel - Stradal, J. Ryan (New York : Pamela Dorman Books/Viking, 2023)
"This novel is the story of Mariel and Ned, a couple from two very different restaurant families in rustic Minnesota, and the legacy of love and tragedy, of hardship and hope, that unites and divides them"--.
new book 2023 spring.
Keywords: Family life; Women; Man-woman relationships; Family-owned business enterprises; Restaurants; Novels